PENYULUHAN TENTANG ANALISIS BIAYA BERBANTUAN BREAK EVEN POINT DALAM MENCAPAI TARGET LABA - Choiruddin Choiruddin; Maria Maria; Desi Indriasari; Anggun Sapitri (Politeknik Negeri Sriwijaya, 2024)
CV Agro Mandiri Internusa, is one of the entities that contributes to the economy in the city of Palembang. This operates in peeled coconut, coconut milk, and copra products. As a business that carries out production activities, CV Agro Mandiri Internusa requires analytical methods or tools for cost classification, profit planning or desired sales. In connection with this, the team implementing service program activities from the Indonesian National Police accounting department had the opportunity to help CV Agro Mandiri Internusa. The team implementing service activities provides counseling and assistance in determining profit planning with the help of Break Even Point (BEP) analysis. With this service activity, business owners know the costs incurred in making the product until the product is handed over to the consumer. The final result of the activity is that managers can determine profit planning according to the costs incurred to produce products which previously were only based on predictions without the support of accurate data. In this way, owners/managers can determine sales (selling price and sales volume), accurate profit planning so that the desired profit achievement is measurable